Regulated coexpression of PrP from different species in mice impacts the replication and host range properties of prion strains - Joseph P. DeFranco; Jifeng Bian; Sehun Kim; Zoe N. Atkinson; Jenna Crowell; Hae-Eun Kang; Hannah O. Bodrogi; Jeffrey R. Christiansen; Carlos M. Díaz-Domínguez; Glenn C. Telling (Proceedings of the National Academy of Sciences, 2025)
Our previous demonstration that replacement of murine cellular prion protein (PrP C ) expression with elk or deer PrP C eliminated the resistance of mice to chronic wasting disease (CWD) prions from deer, elk, and other cervids highlighted the importance of sequence homology between PrP C and its conformationally altered counterpart (PrP Sc ) for optimal prion replication. To further investigate the effects of species-specific PrP primary structural variation on the evolution of prion host range and strain properties during interspecies transmissions, we generated mice with precisely controlled expression of both murine and either deer or elk PrP C and challenged them with cervid or murine prions. While CWD prion transmission was inhibited to varying degrees under these conditions, the strain properties and species specificities of the resulting cervid prions were not impacted. By contrast, although murine prions induced conformational conversion of mouse but not coexpressed cervid PrP C , the resulting prions produced disease in mice expressing either cervid or mouse PrP C . Our findings show that while mouse PrP C inhibited conformational conversion of deer or elk PrP C without affecting the host range of CWD prions, coexpression of cervid PrP C influenced the selection of strains with expanded host range properties during conformational conversion of mouse PrP C by murine prions. Our studies reveal diverse influences of bystander PrP C expression on the replication, host range, and strain properties of prions generated during conformational conversion of their coexpressed cognate PrP C . These cooperative or inhibitory effects occur in trans and derive from species-specific primary structural variations between coexpressed PrP C substrates and infectious prions.